2012
DOI: 10.1111/j.1464-410x.2011.10883.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear matrix protein‐22: a prospective evaluation in a population at risk for bladder cancer. Results from the UroScreen study

Abstract: What ' s known on the subject? and What does the study add?The prognosis of bladder cancer signifi cantly depends on tumour stage and time of diagnosis so early diagnosis is desirable to decrease mortality and treatment costs. The NMP22 test is approved for clinical application by the Food and Drug Administration (FDA) of the US. Previous studies have reported values of 47 -100% for sensitivity and 58 -91% for specifi city with this test, but there is no new data on the predictive value of NMP22 for screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…Unfortunately this performance has not always been reproduced when the assays are evaluated in independent patient populations (Table 1). 25,26 This finding is most evident from the results of the UroScreen study, wherein NMP22® was used to screen a population with a high risk of bladder cancer owing to previous chemical exposures; the specificity of NMP22® was found to be only 29%. 25 A similar observation was evident for the UroVysion® assay, in which the reported sensitivity was only 45%.…”
Section: Currently Available Urine Testsmentioning
confidence: 77%
See 1 more Smart Citation
“…Unfortunately this performance has not always been reproduced when the assays are evaluated in independent patient populations (Table 1). 25,26 This finding is most evident from the results of the UroScreen study, wherein NMP22® was used to screen a population with a high risk of bladder cancer owing to previous chemical exposures; the specificity of NMP22® was found to be only 29%. 25 A similar observation was evident for the UroVysion® assay, in which the reported sensitivity was only 45%.…”
Section: Currently Available Urine Testsmentioning
confidence: 77%
“…25,26 This finding is most evident from the results of the UroScreen study, wherein NMP22® was used to screen a population with a high risk of bladder cancer owing to previous chemical exposures; the specificity of NMP22® was found to be only 29%. 25 A similar observation was evident for the UroVysion® assay, in which the reported sensitivity was only 45%. 26 ImmunoCyt™ also proved to be less effective when tested in 506 patients with atypical urinary cytology, resulting in a specificity of 49%.…”
Section: Currently Available Urine Testsmentioning
confidence: 77%
“…In a recent study which enrolled 1609 risky factory employees who were working with a chemical substance containing aromatic amine, diagnostic sensitivity, specificity, negative, and positive predictive values of NMP22 test were 97.2, 28.5, 99, and 12.2%, respectively. [9] In a study performed by Tritschler et al [5] on 100 patients without previous diagnosis of bladder cancer, sensitivity, and specificity of the NMP22 test, and cytology were found to be 65 vs 44%, and 40 vs. 78%, respectively. The authors concluded that with lower sensitivity, and specificity rates NMP22 could not be recommended in daily practice as a bedside test in the diagnosis, and monitorization of the bladder cancer.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, postresection monitoring in bladder cancer patients may involve both cytology and other biomarker-based methods (e.g., detection of nuclear matrix protein 22). However, the utility of these newer approaches is not universally accepted, especially across distinct patient populations and clinical situations (35), and additional biomarkers and methodologies are under study. Topical administration of an exfoliant would provide a much richer sample for cytologic analysis, likely increasing the sensitivity of cell-based diagnostics.…”
Section: Discussionmentioning
confidence: 99%